Does Mandatory Adoption of IFRS Improve Accounting Quality? Preliminary Evidence1. (16th April 2013) - Ahmed, Anwer S.; Neel, Michael; Wang, Dechun
Abstract : We provide evidence on the preliminary effects of mandatory adoption of International Financial Reporting Standards (IFRS) on accounting quality for a relatively broad set of firms from 20 countries that adopted IFRS in 2005 relative to a benchmark group of firms from countries that did not adopt IFRS matched on the strength of legal enforcement, industry, size, book‐to‐market, and accounting performance. Relative to these benchmark firms, we find that IFRS firms exhibit significant increases in income smoothing and aggressive reporting of accruals, and a significant decrease in timeliness of loss recognition; however we do not find significant differences across IFRS and benchmark firms in meeting or beating earnings targets. Our findings contrast with findings in earlier studies which suggest that IFRS adoption leads to increased accounting quality. Our findings primarily hold for firms in strong enforcement countries, which suggests that enforcement mechanisms in these countries were not able to counter the initial effects of greater flexibility in IFRS relative to domestic GAAP.